Photosynthetic pigment content alterations in Arachis hypogaea L. in relation to varied irrigation levels with growth hormone and triazoles - Karthishwaran, R. Somasundaram, B. Sankar, K. (Journal of Ecobiotechnology, 2016)
Â Â Â Â Â Â Â Â Â Â Â Field experiments were conducted to identify the variation of photosynthetic pigment contents in peanut under drought stress, paclobutrazol (PBZ) and abscisic acid (ABA) and their combination. The pigment contents of the groundnut leaves increased with age in control and treatments. Drought stress decreased the chlorophyll, carotenoid, xanthophyll and anthocyanin contents. PBZ and ABA to the drought stressed plants increased the chlorophyll, carotenoid, xanthophyll and anthocyanin contents when compared to stressed and unstressed plants.